SEVERE CROWDING WITH UPPER MIDLINE SHIFT ASSOCIATED WITH AN SUPERNUMERARY TOOTH: A CASE REPORT - Daniela Anistoroaei; Georgeta Zegan; Iulia Catalina Saveanu; Alina Sodor; Loredana Golovcencu (Romanian Dental Association for Education, 2018)
Supernumerary tooth represents a developmental anomaly that consists in duplication of tooth in the normal series. The presence of a supernumerary tooth may result in the appearance of aesthetic or functional problems in the dento-maxillary system. A girl, 11 years old, with upper midline shift following a supernumerary teeth and severe upper crowding was successfully treated after extraction of supernumerary tooth and four first bicuspids. Stages of diagnosis and treatment have been described in detail. In order to obtain good treatment results it was necessary to use an asymmetrical orthodontic mechanic. In this case report, the diagnostic workflow and current treatment concepts was presented and critically discussed.